2016
DOI: 10.1371/journal.pone.0154239
|View full text |Cite
|
Sign up to set email alerts
|

Jellyfish Stings Trigger Gill Disorders and Increased Mortality in Farmed Sparus aurata (Linnaeus, 1758) in the Mediterranean Sea

Abstract: Jellyfish are of particular concern for marine finfish aquaculture. In recent years repeated mass mortality episodes of farmed fish were caused by blooms of gelatinous cnidarian stingers, as a consequence of a wide range of hemolytic, cytotoxic, and neurotoxic properties of associated cnidocytes venoms. The mauve stinger jellyfish Pelagia noctiluca (Scyphozoa) has been identified as direct causative agent for several documented fish mortality events both in Northern Europe and the Mediterranean Sea aquaculture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
(55 reference statements)
3
16
0
Order By: Relevance
“…Consequences of Cnidaria stings may range from minor local irritation to severe local and systemic reactions including excruciating pain and life-threatening cardiovascular collapse depending on the Cnidarian species, age of the victim and size of the area contacted. In addition, Cnidarians outbreaks may interfere with human activities such as tourism, bathing, aquatic events, fishing and aquaculture, causing substantial economical burden1234. On the other hand, Cnidarians venom is a rich source of bioactive substances that may have therapeutic potential and other useful applications567.…”
mentioning
confidence: 99%
“…Consequences of Cnidaria stings may range from minor local irritation to severe local and systemic reactions including excruciating pain and life-threatening cardiovascular collapse depending on the Cnidarian species, age of the victim and size of the area contacted. In addition, Cnidarians outbreaks may interfere with human activities such as tourism, bathing, aquatic events, fishing and aquaculture, causing substantial economical burden1234. On the other hand, Cnidarians venom is a rich source of bioactive substances that may have therapeutic potential and other useful applications567.…”
mentioning
confidence: 99%
“…Experimental studies with the scyphozoan A. aurita showed gill epithelium recovery required 2 weeks after even brief (10 h) contact between jellyfish and salmonids (Baxter et al, 2011b). Equally, laboratory experiments carried out by Bosch-Belmar et al (2016b), demonstrated partial recovery of sea bream gill tissue after 3 weeks from fish exposure to medium densities of P. noctiluca. These gill disorders used to pass unnoticed, but the consequences of this stressful situation (repeated contact with jellyfish) could be severe, and even if fish gill epithelium could FIGURE 7 | Generalized linear model between total gill score and cnidarian density for the Almería facility (above) and the Málaga fish farm (below).…”
Section: Discussionmentioning
confidence: 99%
“…Tiny and almost transparent medusae, siphonophores, and hydrozoan larvae may easily remain unnoticed to aquaculture operators, but they can develop high density blooms, be inhaled by fish, and inflict severe damage due to nematocyst discharge and consequent tissues envenomation (Fosså et al, 2003). A range of morphological injuries caused by contacts with cnidarian stinging cells have been described on several cultured fish species (Baxter et al, 2011b;Bosch-Belmar et al, 2016b;Marcos-López et al, 2016). Available evidence shows that a few hours of exposure to stinging cells may lead to severe damage at cellular, tissue and systemic levels, including changes in fish metabolic performances (BoschBelmar et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…were obtained from an aquaculture facility near Licata (Sicily, Italy). The choice of juveniles was related to severe mortality events caused by jellyfish in different Mediterranean aquaculture facilities where the most affected fish class ranged 15–60 g in weight 28 .…”
Section: Methodsmentioning
confidence: 99%
“…Beyond these few studies, limited information is available on how jellyfish affect fish health, the biological mechanisms underlying fish mortalities, or estimates of potential economic losses 21 . Only a few studies described significant fish injuries caused by the discharge of cnidocytes (specialized cnidarian stinging cells) in fish tissues (skin, gills) leading to envenomation and cellular damage 23 28 .…”
mentioning
confidence: 99%